Volume of wastewater discharged from Australian Antarctic Stations - PRICE, TIM (hasPrincipalInvestigator); PRICE, TIM (processor); Australian Antarctic Data Centre (publisher)
This indicator is no longer maintained, and is considered OBSOLETE. INDICATOR DEFINITION This is an estimate of the volume of effluent discharged from the waste treatment plants (WTP) at each of the three continental stations. Measurements are continuous and are reported monthly, in the station plumbers' reports to the Building Services Supervisor in Kingston. TYPE OF INDICATOR There are three types of indicators used in this report: 1.Describes the CONDITION of important elements of a system; 2.Show the extent of the major PRESSURES exerted on a system; 3.Determine RESPONSES to either condition or changes in the condition of a system. This indicator is one of: PRESSURE RATIONALE FOR INDICATOR SELECTION This indicator gives an estimate of the volume of wastewater discharged into the ocean as a result of human occupation, and hence of the potential to contaminate the ocean. The potential impact on the environment is proportional to the volume discharged. Estimates of microbial levels and organic matter content of the effluent give more specific details. Discharges from the waste treatment plants at the stations comprise virtually all wastewater discharge into the ocean from the stations. Water flowing into the sea along natural flow lines may contain some contaminants, for example as a result of fuel spills. However, these are usually minimal, and any major incidents will be accounted for in other reports. Reporting figures monthly allow comparison of summer and winter usage, and therefore any effects of typically high summer and low winter populations. Effluent volumes are also an indicator of the volume of water harvested, as there is a predictable relationship between water harvested and that released. This information can be used (together with potable water volumes) as a measure of the effectiveness of any station water conservation measures. Water usage has implications for fuel usage, as fuel is used to melt water for domestic use and to operate the WTPs. DESIGN AND STRATEGY FOR INDICATOR MONITORING PROGRAM Spatial scale: Australian Antarctic continental stations and Macquarie Island station. Frequency: Monthly reports Measurement technique: The rate of discharge of effluent is estimated from measurements of flow rates through the effluent pump. Measurements, in litres, are continuous, and recorded whenever the pump is working. A flow meter has been installed at Casey and monitors the volume, in litres, of effluent as it flows out the pipe. RESEARCH ISSUES The following would increase knowledge of the impacts of wastewater discharge: Equipment which could monitor effluent release directly, rather than estimating values from the flow rate in pumps would give more accurate figures. Chemical analysis of effluent eg for phosphate. This would indicate the extent of enrichment as a result of wastewater discharge, and would allow feedback to management on issues such as, the types of washing detergent supplied at stations. An analysis of the properties and proportion of various effluent water types would provide useful feedback to station management on wastewater plant efficiency and assist in determining outfall effects. LINKS TO OTHER INDICATORS SOE Indicator 48 - Station and ship person days SOE Indicator 51 - Biological oxygen demand of wastewater discharged from Australian Antarctic Stations SOE Indicator 52 - Suspended solids content of wastewater discharged from Australian Antarctic Stations SOE Indicator 61 - Total potable water consumption